2011
DOI: 10.1158/0008-5472.can-10-3994
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-23 Monoclonal Antibody Synergizes in Combination with Targeted Therapies or IL-2 to Suppress Tumor Growth and Metastases

Abstract: Immunosuppressive barricades erected by tumors during the evolution of immune escape represent a major obstacle to many potentially effective cancer therapies and vaccines. We have shown that host interleukin (IL)-23 suppresses the innate immune response during carcinogenesis and metastasis, independently of effects on the proinflammatory cytokine IL-17A. Based on these findings, we envisioned that IL-23 neutralization might offer a promising strategy to modulate immunosuppression, particularly in combination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…Recently, we reported that a neutralizing monoclonal antibody (mAb) to mouse IL-23p19 alone suppressed early experimental B16F10 melanoma lung metastases and modestly inhibited subcutaneous tumor growth. More importantly, the use of anti-IL23p19 mAb in combination with IL-2 or anti-erbB2 mAb treatment significantly inhibited subcutaneous growth of established mammary carcinoma and suppressed established experimental and spontaneous lung metastases (5). Overall, these data suggest that IL-23 is an important immunosuppressive cytokine in developing tumors and metastases and that targeting IL-23 in combination with other promising immune targets is a rational and effective means to treat cancer.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, we reported that a neutralizing monoclonal antibody (mAb) to mouse IL-23p19 alone suppressed early experimental B16F10 melanoma lung metastases and modestly inhibited subcutaneous tumor growth. More importantly, the use of anti-IL23p19 mAb in combination with IL-2 or anti-erbB2 mAb treatment significantly inhibited subcutaneous growth of established mammary carcinoma and suppressed established experimental and spontaneous lung metastases (5). Overall, these data suggest that IL-23 is an important immunosuppressive cytokine in developing tumors and metastases and that targeting IL-23 in combination with other promising immune targets is a rational and effective means to treat cancer.…”
Section: Introductionmentioning
confidence: 78%
“…1 Cancer Immunology Program, Trescowthick Laboratories, Peter MacCallum Cancer Centre, St. Andrews Place, East Melbourne; 2 Sir Peter MacCallum Department of Oncology, University of Melbourne, Parkville, Victoria; 3 Immunology in Cancer and Infection Laboratory; 4 Cancer Immunoregulation and Immunotherapy Laboratory, Queensland Institute of Medical Research; 5 School of Medicine, University of Queensland, Herston, Queensland, Australia; and 6 AMGEN Incorporated, Seattle, Washington mAb combination is superior to either therapy alone and the effect is NK/T-and IL-12p35 dependent.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46] Whereas in B16 melanoma this effect was mediated by a subset of innate lymphoid cells (ILCs), the By using mice lacking IL-23, IL-23 receptor or anti-IL23p19 blocking antibodies, endogenous IL-23 was shown to promote tumor growth in different tumor models. 142,143 In colorectal carcinoma, the effects of IL-23 were mimicked after blocking IL-17A. 144 In DMBA/ TPA-induced skin papillomas and MCA-induced fibrosarcomas, the protumorigenic effects of IL-23 were independent of the main Th17 cytokine.…”
Section: Mechanisms Of Tumor Protection Through Il-12mentioning
confidence: 99%
“…The B16F10 mouse melanoma cell line was chosen on the basis of its high metastatic potential in this study. Specifically, the B16F10 line has been shown to metastasize to the lungs when injected into the lateral tail vein and the majority of cells find themselves in the pulmonary tissue, but some are also localized in other organs [2] and is accepted as useful model for the study of lung metastasis [23]. We showed that the mice received B16F10 cells only implanted, the melanoma cells quite well and the lungs of these hosts were visibly riddled with metastatic tumor nodules within 21 days (Fig.…”
Section: Discussionmentioning
confidence: 72%